OVERVIEW OF DRUG PROCUREMENT MANAGEMENT INDICATORS IN SUKOHARJO CENTRAL JAVA HOSPITAL - Heru Sasongko; Okky Mareta Octadevi (Universitas Sebelas Maret, 2016)
Drug management in hospital is one of important hospital management especially in the planning and procurement stages. Inefficiency can induce bad condition on hospital, both medically and economically. This study was conducted to describe procurement of drugs for public patients in Sukoharjo Regional General Hospital. These stages were chosen because of the success of the drug planning and procurement will greatly determine the quality of the service at the Pharmacy Installation of Hospital.This is non-experimental research with descriptive designs. Data were collected concurently and retrospectively in Sukoharjo Regional General Hospital, a primary and secondary data. Primary data were obtained at the time of the study by conducting in-depth interviews, and secondary data obtained by tracking the documents prior year. The result of this study showed the percentage of available fund compared on total needed fund 96.16% and the percentage of drug items held with the planned was 82.16%, the procurement frequency of each drug item was 1-6 times in annual, drug invoice failure frequency was four times of 41 samples, and the frequency rate of delayed in payment by the hospital to the time agreed was 36.45 days.